(untitled) (Journal of Pathology of Nepal, 2018)
Background: Blood transfusion unit collection, storage and dispatching on Birat Medical College and Teaching Hospital began from 19 June 2016 via blood bank. After which, many blood distribution were made accessible via this service. This study analyzes the blood transfusion request and utilization pattern and also to monitor for managing the bloodstocks meeting present and future demand in hospital. Materials and Methods: This is descriptive cross-sectional study conducted for all the requests of whole blood dispatched from 19th June, 2016 to 04th July, 2018. Whole blood requisitions from various departments were reviewed regarding the number of requisition, total blood unit replaced, blood group and socio-demographic profile of patients. Results: Of 648 transfusion units dispatched, 131 and 324 patients were male and female respectively, B positive blood group were most common, followed by A positive, O positive, AB positive, A negative, O negative and AB negative respectively. The largest numbers of requisitions were from Gynecology and Obstetric department in the hospital of 258 requisitions followed by internal medicine, surgery department, postoperative ward and orthopaedic department. Majority of the requisitions were for 20-29 years age group from the local district Morang. The total blood units replaced were 75, of which 29 and 46 of male and female respectively. Conclusions: B Positive was the predominant requested blood group with Gynecology and Obstetrics department making the most requests, among 20-29 years age group from Morang district. The total replaced blood units were less in number with some requisition forms even lacked essential details.